Virtual ABI: A computationally derived ABI index for noninvasive assessment of femoro-popliteal bypass surgery outcome. (September 2021) - Milasinovic, Danko Z.; Sekulic, Dragan B.; Nikolic, Dalibor D.; Vukicevic, Arso M.; Tomic, Aleksandar P.; Miladinovic, Uros M.; Paunovic, Dragana S.; Filipovic, Nenad D.
Highlights: Peripheral arterial disease (PAD) of the lower limbs affects 12-14% of the population. Ankle-brachial index (ABI) is the standardized method for preoperative screening the PAD. Virtual ABI is computational procedure for assessing outcome of PAD bypass surgery. Virtual ABI utilizes preoperative measurements and blood flow numerical simulations. Correlation of the Virtual ABI with experimentally measured ABI was R² = 0.9485. Abstract: Background and objective: Peripheral arterial disease of the lower limbs, which affects 12-14% of the population, is often treated by bypassing a blocked portion of the vessel. Due to the limited ability of clinicians to predict the outcome of a selected bypass strategy, the five-year graft occlusion ranges from 50% to 90%, with a 20% risk of amputation in the first 5 years after the surgery. The aim of this study was to develop a computational procedure that could enable surgeons to reduce negative effects by assessing patient-specific response to the available surgical strategies. Methods: The Virtual ABI assumes patient-specific finite element modeling of patients' hemodynamics from routinely acquired medical scans of lower limbs. The key contribution of this study is a novel approach for prescribing boundary conditions, which combines noninvasive preoperative measurements and results of numerical simulations. Results: The validation performed on six follow-up cases indicated high reliability of the Virtual ABI, since the correlation with the experimentally measured values of ankle-brachial index was R² = 0.9485. Conclusion: The initial validation showed that the proposed Virtual ABI is a noninvasive procedure that could assist clinicians to find an optimal strategy for treating a particular patient by varying bypass length, choosing adequate diameter, position and shape. Graphical abstract: Image, graphical abstract